KEEFEKTIFAN DOSIS TEPUNG BIJI SRIKAYA (Annona squamosa L.) DALAM MENGENDALIKAN HAMA BUBUK KEDELAI (Callosobruchus analis F.) DI PENYIMPANAN - Rahmiyul Insani; Desita Salbiah (DINAMIKA PERTANIAN, 2021)
Soybean is an important food crop in Indonesia, which contains a lot of protein and is useful as an industrial ingredient and animal feed. Callosobruchus analis F. is a pest that causes a decrease in soybean production in storage. The suggestion recommended is to use plant based insecticides by using custard apple seed (Annona squamosa L.). This research aims to obtain a dose of custard apple seed flour (Annona squamosa) that is effective in controlling soy pest Callosobruchus analis in stored soybean seeds. The research was conducted at the Plant Pest Laboratory of Faculty of Agriculture, Riau University, from July to October 2019. The study was carried out using a completely randomized design with 6 treatments and 4 replications. The dose treatment of custard apple seed flour was given to each experimental unit was 0 g.100 g-1 soybean seeds, 2 g.100 g-1 soybean seeds, 4 g.100 g-1 soybean seeds, 6 g.100 g-1 soybean seed, 8 g.100 g-1 soybean seed and 10 g.100 g-1 soybean seed. The results showed that the provision of custard apple seed flour at a dose of 4 g.100 g-1 of soybean seeds was effective in killing C. analis pests. This could cause a total mortality of 80% with early death of 14.50 hours after application and LT50 34.00 hours after application with an individual increase of 19.25 C. analis pests with a percentage of weight depreciation of soybean seeds of 1.93%.